Voennyi kur'er . Voennyi kur'er . Military Messenger . Военный курьер - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Segment on the Moscow Suvorov Military School; military news. Featured in the program: Yeltsin, Boris Nikolayevich (President of the Russian Federation) Contributors: Krondo, Igor' (Anchor) Сюжет о Московском Суворовском Училище; военные новости. В программе участвуют: Ельцин, Борис Николаевич (Президент Российской Федерации) Создатели: Крондо, Игорь (Ведущий/Ведущая)